New Mexican variety of poinsettia called Victoria - Canul-Ku, Jaime; García-Pérez, Faustino; Barrios-Gómez, Edwin Javier; Rangel-Estrada, Sandra Eloísa (Revista Mexicana de Ciencias Agrícolas, 2022)
The state of Morelos is characterized by the diversity of ornamental species that are grown and marketed both in the national and international market. In Mexico, approximately 20 million plants finished in different container sizes are marketed annually, with a production value of 718 million. Genetic improvement programs for cultivated species run by government agencies are scarce. The largest proportion is carried out by foreign private companies. Poinsettia is subjected to the same model. Faced with this situation, the National Institute of Forestry, Agricultural and Livestock Research launched the Poinsettia Genetic Improvement Program in the Experimental Field of Zacatepec, Morelos. The poinsettia variety called Victoria is a product of this program and was generated through hybridization, selection and grafting technique. Victoria is an intermediate plant with medium branching and width. The outstanding attributes of this variety are the oval shape of the leaf, the size of the leaf and the absence of lobes. The shape of the base of the leaf is rounded. The bracts are elliptical in shape, red in color and of intermediate size. The width of the cyme and the size of the gland are medium. It is considered an intermediate cycle variety. The response of Victoria is statistically comparable to commercial varieties and represents an option for the country’s producers in order to diversify the offer in the Christmas season.